2013
DOI: 10.3109/02656736.2013.823672
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal efficacy of lasers against dermatophytes and yeastsin vitro

Abstract: This study demonstrates a clear thermal effect for linear scanning 980-nm and long-pulsed 1064-nm laser systems on either nail clippings or cell culture media. Complete pathogen growth impairment was achieved if temperatures were measured above 50 °C. The results for the 1064-nm system were almost comparable to 980 nm results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 35 publications
0
21
0
4
Order By: Relevance
“…The development of lasers for onychomycosis is at an important phase, as primary research on fungal chromophores, the thermal properties of fungal hyphae and a clear understanding of laser penetrance through an infected nail plate are crucial to the achievement of effective selective photothermolysis. The results of early in vitro and in vivo studies of lasers in onychomycosis have mostly yielded poor results (2,(29)(30)(31)(32). This is attributable to the use of non-optimal, preexisting laser systems being applied for a new indication without regard for optimization to the fungal target.…”
Section: Discussionmentioning
confidence: 95%
“…The development of lasers for onychomycosis is at an important phase, as primary research on fungal chromophores, the thermal properties of fungal hyphae and a clear understanding of laser penetrance through an infected nail plate are crucial to the achievement of effective selective photothermolysis. The results of early in vitro and in vivo studies of lasers in onychomycosis have mostly yielded poor results (2,(29)(30)(31)(32). This is attributable to the use of non-optimal, preexisting laser systems being applied for a new indication without regard for optimization to the fungal target.…”
Section: Discussionmentioning
confidence: 95%
“…In a study of Paasch et al [8], the highest increase in temperature in a 980-nm laser was found with a pulse of 6 ms and a fluence of 27 J/cm 2 , with an inhibition of growth for Candida guilliermondii and T. interdigitale only at temperatures >50°C. All other pathogenic germs showed reduced, but not inhibited growth, and C. albicans showed no impact at all.…”
Section: Discussionmentioning
confidence: 99%
“…Oceniano zahamowanie wzrostu kolonii grzybów T. rubrum po jednokrotnym zabiegu, a zamierzony efekt osiągnięto przy zastosowaniu lasera Nd:YAG 1064 nm (4 J/cm 2 i 8 J/cm 2 ), Nd:YAG 532 nm (8 J/cm 2 ), a także pulsacyjnego lasera barwnikowego 595 nm (8 J/cm 2 i 14 J/cm 2 ). Zaobserwowano, że lasery generujące promieniowanie o długości 808 nm i 980 nm powodują podgrzanie medium hodowli, również hodowli grzybów, a wykorzystanie większej energii przynosi lepsze efekty, ale może być bardziej bolesne [14]. Autorzy zwrócili uwagę na fakt, że naświetlanie nie zawsze powoduje inaktywację grzybów, zwłaszcza T. rubrum i T. interdigitale.…”
Section: Promieniowanie Laserowe W Leczeniu Grzybicy Paznokciunclassified
“…Autorzy zwrócili uwagę na fakt, że naświetlanie nie zawsze powoduje inaktywację grzybów, zwłaszcza T. rubrum i T. interdigitale. Niekiedy może dochodzić do wzrostu kolonii grzybów po naświetlaniach, co autorzy łączą z możliwością wystąpienia efektu biostymulującego [14].…”
Section: Promieniowanie Laserowe W Leczeniu Grzybicy Paznokciunclassified